Effect of population dynamics and mechanization on agricultural land use: evidence from Nang Rong, Thailand - Piyawat Katewongsa (2014)
This study examines the effects of population dynamics and the role of agricultural machinery on agricultural land use in Nang Rong district, Thailand between 1994 and 2000. The unit of analysis is the household, using data from a sample of 5,255 households. The results show that population dynamics continuously influenced agricultural land use. Migration was the most influencing factor among population dynamic indicators; it had negative effects on land use for rice and field crops, but positive effects on multiple and rotation crops. Death events had some negative effects on land use for field crops, while in-migration had positive effects on rice growing. Agricultural machinery factors produced a great influence on land use changes both in terms of number and size of plots, and play an essential role in the enhancement of agricultural practices. In conclusion it is important to recognize that the effect of population dynamics and the use of agricultural machinery are key indicators that result in crucial influences on land use.